1976
DOI: 10.1139/b76-060
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of tissue chlorogenic acid concentrations and leaching of phenolics from sunflowers grown under varying phosphate nutrient conditions

Abstract: 1976. The relationship of tissue chlorogenic acid concentrations and leaching of phenolics from sunflowers grown under varying phosphate nutrient conditions. Can. J. Bot. 54: 593-599. A large increase in the concentration of the isomers of chlorogenic acid was observed in extracts of sunflowers grown under phosphate-deficient conditions when compared with phosphate-sufficient plants. More phenolic compounds were leached from living intact roots, dried roots, and tops of phosphate-deficient plants than from pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0
1

Year Published

1984
1984
2003
2003

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(18 citation statements)
references
References 29 publications
3
14
0
1
Order By: Relevance
“…The authors identified phenolic-like compounds released by roots as agents affecting Fe 3+ reducing activity in the growth medium. Phenolic compounds have been reported as active P mobilizing agents in soil minerals (Koeppe et al, 1976). Our results on soil-grown tall fescue suggest that N. coenophialum-endophyte, unlikely mycorrhizal fungi in other grasses, might be involved indirectly in modifications of root functions in tall fescue grown in P-deficient soils.…”
Section: Endophyte Effects On Phosphorus Acquisition In Tall Fescuementioning
confidence: 57%
“…The authors identified phenolic-like compounds released by roots as agents affecting Fe 3+ reducing activity in the growth medium. Phenolic compounds have been reported as active P mobilizing agents in soil minerals (Koeppe et al, 1976). Our results on soil-grown tall fescue suggest that N. coenophialum-endophyte, unlikely mycorrhizal fungi in other grasses, might be involved indirectly in modifications of root functions in tall fescue grown in P-deficient soils.…”
Section: Endophyte Effects On Phosphorus Acquisition In Tall Fescuementioning
confidence: 57%
“…However, the ability of a wide range of abiotic stress factors to stimulate phenylpropanoid biosynthesis is less widely appreciated. These abiotic factors include high light (Mole et al 1988;Beggs & Wellman 1994), low temperatures (Christie et al 1994;Solecka et al 1999), sugars (Tsukaya et al 1991;Sadka et al 1994) and phosphate de¢ciency (Koeppe et al 1976;Trull et al 1997;Yamamoto et al 1998). Although the signal transduction pathway that triggers this common biosynthetic response to diverse environmental factors is not fully understood, cellular bioenergetics are thought to play a crucial role in regulating key elements of the pathway (Ehness et al 1997).…”
Section: Bioenergetics Of Phenolic Metabolism In Stress Responsesmentioning
confidence: 99%
“…It has been also reported that large amounts of allelochemical compounds were leached from the living intact roots, dried roots, and tops of phosphate deficient plants than from phosphate sufficient ones. [75] Phosphorus deficiency is one of the most important yield limiting nutrient for upland rice in Brazilian Oxisol. [76] Hence, P deficiency may aggravate allelopathy problem in upland rice grown on Brazilian Oxisols.…”
Section: Planting Allelochemical Resistant Cultivarsmentioning
confidence: 99%